ESSMENT OF RISK FOR OSTEOPOROSIS AMONG POSTMENOPAUSAL WOMEN - S. KALA BARATHI; Dr. S. KALAVATHI (International Journal of Pharma and Bio Sciences, 2016)
Osteoporosis is a condition in which bones weaken and are more likely to fracture. Fractures from osteoporosis can result in pain and disability. As the population continues to age, morbidity and mortality from fractures due to low bone mineral density (BMD) will likely continue to increase especially among women in Postmenopausal period. Objective to assess the risk for Osteoporosis among postmenopausal women, and to determine the association of risk with the demographic variables. A descriptive observational study was used to assess the risk for Osteoporosis. Among 100 postmenopausal women (31%) were high risk for osteoporosis, 25(25%) were found to be having moderate risk and 44 (44%) were in the low risk group. It was also found that the dietary life style of post menopausal women was found to be highly significant at p = 0.05, S* The OSTA index, a simple and free risk assessment tool, can be used to estimate the prevalence of risk for osteoporosis among Postmenopausal women. Efforts should be made to screen those at risk for osteoporosis, identify and address various risk factors for falls and associated fractures, ensure adequate calcium and vitamin D intake, and institute pharmacological therapy to increase BMD if necessary.